1997
DOI: 10.1103/physrevb.56.r12741
|View full text |Cite
|
Sign up to set email alerts
|

Scaling and the metal-insulator transition in Si/SiGe quantum wells

Abstract: The existence of a metal-insulator transition at zero magnetic field in two-dimensional electron systems has recently been confirmed in high mobility Si-MOSFETs. In this work, the temperature dependence of the resistivity of gated Si/SiGe/Si quantum well structures has revealed a similar metal-insulator transition as a function of carrier density at zero magnetic field. We also report evidence for a Coulomb gap in the temperature dependence of the resistivity of the dilute 2D hole gas confined in a SiGe quantu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
55
0

Year Published

1999
1999
2007
2007

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(59 citation statements)
references
References 17 publications
4
55
0
Order By: Relevance
“…20.Dx Electron states in low-dimensional structures -72. 10.Bg General formulation of transport theory -05.60.Gg Quantum transport…”
Section: November 6 2000mentioning
confidence: 99%
“…20.Dx Electron states in low-dimensional structures -72. 10.Bg General formulation of transport theory -05.60.Gg Quantum transport…”
Section: November 6 2000mentioning
confidence: 99%
“…The associated metal-toinsulator transition (MIT) has subsequently become the subject of intense interest and controversy [3]. While behavior similar to that of Ref.[2] has now been reported for a wide variety of 2D carrier systems such as n-AlAs, 10], and p-Si/SiGe [11,12], the origin of the metallic state and its transition into the insulating phase remain major puzzles in solid state physics.Several experiments have demonstrated the important role of the spin degree of freedom in the MIT problem, either in systems with a strong spin-orbit interaction [10,13,14], or via the application of an external magnetic field to spin polarize the carriers [15,16,17,18,19]. The latter experiments have shown that a magnetic field applied parallel to the 2DES plane suppresses the metallic temperature dependence, ultimately driving the 2DES into the insulating regime as the 2DES is spin polarized.…”
mentioning
confidence: 99%
“…While behavior similar to that of Ref. [2] has now been reported for a wide variety of 2D carrier systems such as n-AlAs [4], n-GaAs [5], n-Si/SiGe [6,7], p-GaAs [8,9,10], and p-Si/SiGe [11,12], the origin of the metallic state and its transition into the insulating phase remain major puzzles in solid state physics.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The 2D systems that show the MIT [1][2][3][4][5][6] are characterized by strong Coulomb interaction between electrons. The mean Coulomb energy per electron U = (πN s ) 1/2 e 2 /4πε 0 κ is larger than the mean kinetic energy K = πh 2 N s /m * by an order of the magnitude around the critical point for the MIT.…”
mentioning
confidence: 99%